Stress relaxation after low and high-rate deformation of polyurethanes - Commins, T; Siviour, C (Royal Society, 2023)
Polymers possess a wide range of mechanical behaviours depending upon the temperature and loading rate. An often-overlooked aspect is relaxation, important because it acts over a wide range of time periods and begins as soon as the polymer is loaded. In the research presented here, the relaxation behaviour of two polyurethanes (PUs) following deformation was investigated at low-rate, 10-3 s-1, and dynamic, 103 s- 1, loading rates, with the former exploring temperatures from 20 °C to - 60 °C. These are compared to a predictive Prony series model calibrated using mastercurves produced by applying time-temperature superposition to data obtained using a dynamic mechanical analysis machine. For relaxation after dynamic loading, a recently proposed analysis was used to account for the movement of the bars during the relaxation. The model was able to predict the stress-time response after low-rate deformation to strains of 2 %, at all temperatures. As the strains increased, irrecoverable deformation was observed and the model became less accurate. In the dynamic experiments, the model accurately predicted the early stages of relaxation for both PUs but deviated later on. A modification to the model was suggested to account for these observations. Further characterisation of the mechanical response under large strain compressive loading is also reported.